SYSTEM ANALYSIS OF PUBLIC ADMINISTRATION AND GOVERNANCE IN THE CONTEXT OF THE INTERRELATION OF PUBLIC POLICY, NATIONAL SECURITY, AND INSTITUTIONAL CAPACITY OF THE STATE - SYTNYK, Hryhoriy; KOMAHA, Larisa; OREL, Mariia; TKACHENKO, Ihor (Herald of Khmelnytskyi National University. Economic sciences, 2024)
This article focuses on the institutional capacity of the state, which is manifested through the effectiveness of political and administrative processes that ultimately reflect the citizens’ need for security. Therefore, a systematic analysis of the interrelation between public administration and governance in the context of public policy and national security, considering the institutional capacity of the state, is relevant. The effectiveness of administrative decisions depends on a systematic understanding of the interrelation between public policy, public administration, and governance. This influences the reflection of the properties and relationships of political, public, state, and other administrative decisions regarding national security and the institutional capacity of the state. In this context, it is important to reveal the essence and interrelation of social phenomena denoted by the terms "public policy," "public administration," and "public governance," which allows avoiding ambiguity and contradictions in the preparation of administrative decisions. Despite attempts by scholars to bring the content of these concepts to a form that allows them to be operated in the process of solving administrative tasks, factors that determine the security component of these concepts and the institutional capacity of the state remain outside the scope of attention. This underscores the relevance of studying the institutional capacity of the state in the context of modern concepts of public administration and governance, public policy, and national security as social phenomena. The purpose of this work is to comprehend the interrelation of public administration and governance, public policy, and national security in the context of the institutional capacity of the state. The methodological basis is formed by the use of interdisciplinary and systematic approaches, as well as abstract-logical methods. The scientific novelty lies in identifying and proving the importance of a systematic analysis of the interrelation between the institutional capacity of the state, public policy, public administration and governance, and national security, as these social phenomena reflect people’s need for security, meaning that any decisions by public authorities should not lead to threats to national security. It has been found that the human instinct for self-preservation determines the motivation and goals of administrative decisions as a way of responding to threats to social systems. It is substantiated that administrative processes in social systems and the analysis of the functional tasks of administrative entities should be carried out in the context of the modes of existence of systems and their security. Methodological differences in the goal-setting of public administration and governance entities in the context of the dynamics of crisis situations have been identified, generating two groups of goals: managing the probability of a crisis situation and managing the level of protection of individuals, society, and state institutions. The decisive role of public administration entities in public policy and its focus on the realization of national interests has been demonstrated. It has been found that the mission of public administration and governance is to systematically influence all spheres of society to maintain its integrity and sustainable development, therefore their goal-setting is determined by public policy at the strategic level of governance. Attention is drawn to the fact that, despite the similarity of technologies for making state-political and state-administrative decisions, their consequences for the security of social systems differ significantly due to the degree of uncertainty of the factors influencing these decisions. It has been found that the focus in understanding the essence of public administration and governance should be on their goals, defined in the context of the influence of social institutions on social processes, the effectiveness of which determines the security of social systems at the stage of their functioning and development.